Investigation of tensile properties of 316L stainless steel with micro-nano-structure in SEM by in situ tension. Issue 181 (13th June 2017) - Jie, Sheng; Junchen, Li; Peiqing, La; Fuan, Wei; Yi, Song; Keliang, Wang
ABSTRACT: Micro-nano-structure of 316L austenitic stainless steel was taken as an object of study, which prepared by aluminothermic reaction casting. Uniaxial tensile tests were carried out at the RT, and mechanical properties were compared on various process conditions. The best match of strength and ductility was obtained for this condition when rough rolling of 316L stainless steel with micro-nano-structure in as-cast by thermal annealing process with 800°C with a rolling deformation of 40%, and then reducing the temperature to 600°C with a rolling deformation of 70%. The specimen was chosen for in situ observation. Samples of these materials provided dynamic recording of the entire process from initial loading to damage by SEM combined with in situ tension station equipment. The results showed that crack nucleation was found at notch root, as tensile stress was 316 MPa, the location where the maximum principal stress and juncture between austenite phase and ferrite phase. The tensile strength was 815 MPa and elongation-to-failure of about 22%.